Gênero Frustulia Rabenhorst, 1853 (Bacillariophyceae) em igarapés da Região da Calha Norte (Pará - Brasil): taxonomia - SANTOS, Kesiane Magno (Universidade Federal do Oeste do Pará, 2023)
The Amazon hydrographic basin constitutes the largest hydrographic network on the planet. It is composed of several types of water bodies from large rivers, lakes and numerous small streams. Studies in the aquatic environments of the Amazon have shown a high species richness of the genus Eunotia and Pinnularia, being scarce for the genus Frustulia, for example. For the State of Pará, the pioneer contribution of material for Bacillariophyceae was carried out by Dickie, with samples from the Trombetas, Tapajós and Tocantins rivers and from the cities of Óbidos and Santarém. The main objective of the present work was to carry out a taxonomic study of Frustulia species and their distribution in Amazonian streams. Collections were carried out in six streams in January and December in the Calha Norte region in the municipalities of Alenquer and Monte Alegre, State of Pará. The plankton samples were obtained using a net and the periphyton samples by collecting and removing diatoms attached to rocks and plants. Permanent slides containing oxidized material were made. A total of 13 taxa were identified, one species, F. quadrissinuata, the first citation for the Brazilian Amazon, and four pioneer citations for the state of Pará: F. acidophilissima, F. crassinervia, F. saxoneotropica and F. undosa. On the other hand, F. saxonica and F. undosa were common in all analyzed streams. Considering the enormous presence of the network of igarapés in the region studied, where there are, until now, environments not explored by scientists, we consider that the identification of the flora of the genus Frustulia is in its initial phase and the continuity of the studies is necessary to expand the knowledge of that genus and other representatives of microalgae.